2019
DOI: 10.1038/s41598-019-46248-y
|View full text |Cite
|
Sign up to set email alerts
|

A general non-rectangular hyperbola equation for photosynthetic light response curve of rice at various leaf ages

Abstract: Photosynthetic light response (PLR) curves of leaves are usually fitted by non-rectangular hyperbola (NRH) equation, and those fitted NRH parameters may change with leaf aging. The objectives of this study were 1) to reveal the response of NRH parameters of rice leaves, light-saturated net photosynthetic rate ( P nmax ), quantum yield of assimilation ( φ ), dark respiration rate ( R d ) and convexity of the curve ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 39 publications
0
22
0
1
Order By: Relevance
“…Spot measurements at 25°C leaf temperature and 500 μl/L CO 2 were also performed during Experiment 2 (n > 4) using the clear leaf cuvette under natural light conditions. The light response curve means were fitted using the following equation (Ögren & Evans, 1993;Xu et al, 2019).…”
Section: Leaf Gas Exchange Measurementsmentioning
confidence: 99%
“…Spot measurements at 25°C leaf temperature and 500 μl/L CO 2 were also performed during Experiment 2 (n > 4) using the clear leaf cuvette under natural light conditions. The light response curve means were fitted using the following equation (Ögren & Evans, 1993;Xu et al, 2019).…”
Section: Leaf Gas Exchange Measurementsmentioning
confidence: 99%
“…This assumption for CQY and CUE constant behavior is not consistent with recent literature in which contrasting results on the topic are reported. For instance, in rice, Xu et al (2019) [39] observed a decline in photosynthetic rate, dark respiration and quantum yield according to leaf aging. In the latter study, both parameters rapidly increased to a maximum around 15 days, to linearly decline as a response to plant aging.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a constant CUE would indicate that plants always present a constant positive respiration rate and that changes in photosynthetic activity would determine limited variations in growth and respiration, both these scenarios being quite unlikely [36]. Many studies have found that changes in the respiration rate during the plant growth cycle are species/cultivar-specific and maintain similar trends as net photosynthesis [38,39,47]. Furthermore, the situation can be different for the same plant species under different environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By simulating light-response curves of photosynthesis ( A n –I curve), NH model has been widely used to obtain key photosynthetic characteristics (e.g., the maximum net photosynthetic rate, A nmax ; light compensation point when A n = 0, I c ; dark respiration rate, R d ) for various species under different environmental conditions (e.g., Ögren & Evans, 1993 ; Thornley, 1998 ; Ye, 2007 ; Aspinwall et al., 2011 ; dos Santos et al., 2013 ; Mayoral et al., 2015 ; Sun et al., 2015 ; Park et al., 2016 ; Quiroz et al., 2017 ; Yao et al., 2017 ; Xu et al., 2019 ; Yang et al., 2020 ; Ye et al., 2020 ). Significant difference between observed A nmax values and that estimated by NH model for various species has been widely reported (e.g., Chen et al., 2011 ; dos Santos et al., 2013 ; Lobo et al., 2014 ; Ogawa, 2015 ; Sun et al., 2015 ; Quiroz et al., 2017 ; Poirier-Pocovi et al., 2018 ; Ye et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%